Pengaruh Model Pembelajaran Learning Cycle Terhadap Capaian Pembelajaran Karya Ilmiah Siswa SMK Migas Inovasi Riau - Muhamad Ridwan; Elvrin Septyanti; Zulhafizh Zulhafizh (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2023)
This research aims to determine the extent of the influence of the learning cycle learning model on the learning outcomes of scientific work material for class XI students at SMK Migas Innovation Riau. The population in this study were all class XI students at SMK Migas Innovation Riau with a sample of 40 students. Class XI OTKP students are taught using the learning cycle learning model and class XI TKJ 1 students are taught using the conventional model. The type of research is experimental. The instrument used is a test. The hypothesis data analysis technique was first tested for Shapiro-Wilk normality and homogeneity using the t test. The test results for the two samples came from a population that was normally distributed and homogeneous, so the researcher gave treatment to both samples. From the results of data analysis, it was obtained that the average learning outcome for students who used the learning cycle model was 81.10 and the average learning outcome for students who were given the conventional learning model was 63.75. To test the hypothesis, the t test was used, from the calculation results a significance level of 0.005 was obtained. It turns out that the significance value is 0.004 < 0.05, so H0 is rejected and H1 is accepted so that it can be concluded that there is a significant influence in the use of the learning cycle learning model on the learning outcomes of scientific work material